2011
DOI: 10.1111/j.1467-789x.2011.00915.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of dropout in weight loss interventions: a systematic review of the literature

Abstract: Attendance and completion of weight loss intervention is associated with better weight loss outcomes; however, attrition is neither consistently reported nor comprehensively explored in the weight loss literature. A systematic review was undertaken to identify factors associated with attrition in weight loss interventions involving overweight or obese (body mass index ≥ 25) adults (18-65 years). Sixty-one studies published before May 2011 and addressing factors associated with weight loss programme attrition w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

47
412
9
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(497 citation statements)
references
References 70 publications
47
412
9
8
Order By: Relevance
“…Moroshko and colleagues did not find that being male or female was a significant influence on dropping out of weight loss interventions [5]. However, they did not use meta-analysis of sex-specific data from within randomised trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moroshko and colleagues did not find that being male or female was a significant influence on dropping out of weight loss interventions [5]. However, they did not use meta-analysis of sex-specific data from within randomised trials.…”
Section: Discussionmentioning
confidence: 99%
“…There was also a trend towards lower participation by men in group-based interventions (24%), compared with individual counselling (29%) or mail/e-mail/internet (34%); however, the male/female mix of the group-based interventions was not specified. In another systematic review [5], sex was not a predictor of dropout in weight loss interventions, suggesting that where men are included in intervention studies, they are no more or less likely than women to withdraw.…”
Section: Introductionmentioning
confidence: 98%
“…Although this expanded access offers substantial promise for increasing the reach of behavioral weight loss treatment, the potential of these programs to achieve population-level weight loss is diminished by the limited initial enrollment and high attrition that are observed in many weight loss treatments. Attrition from weight loss treatments has been the focus of considerable research attention [7], whereas less attention has been given to the first step in utilization: initiating treatment. Many patients with obesity are not seeking weight loss, and many of those who are trying to lose weight are not initiating empirically supported treatments in the first place [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This was the case in the current study, where OHP participant follow-up protocols were much less stringent than in the precursor trial. A recent review of attrition in weight loss trials showed that there were no consistent demographic, weight, or heath behavior profiles that were associated with program dropout [70]. In the OHP, those who completed the program vs. those who dropped out were largely similar, except that younger and heavier participants were more likely to withdraw.…”
Section: Original Researchmentioning
confidence: 99%